English for Banking Training to Improve Communication Skills for Bank Jateng KCP UNNES Semarang Employees - Ummi Nur Laila Sulistyani; Yuliati Yuliati; Almira Irwaniyanti Utami; Aditya Rangga Putra Cahaya; Nira Amalia (Universitas Negeri Semarang, 2025)
Communication skills, particularly those encompassed in the 4C skills framework, are vital for individuals in the 21st-century workforce. In the digital era, where information is exchanged rapidly and extensively, effective communication is crucial for improving job performance and fostering relationships with external parties. This is especially relevant in the service sector, where employees frequently interact with diverse individuals from various cultural and linguistic backgrounds. The training is designed to enhance employee confidence, professionalism, and ability to serve a diverse customer base effectively. Implementing the English for Banking training at Bank Jateng KCP UNNES has resulted in several significant achievements that have contributed to enhancing employees' English language proficiency. These include an enhanced understanding of banking terminology in English, improved active communication skills in English, increased proficiency in handling English-language documents, greater confidence in interacting with foreign customers, the ability to apply English in daily work processes, and strengthened teamwork and collaboration.